Serial Post-mortem Relaxometry in the Normal Rat Brain and Following Stroke - Fagan, Andrew J; Mullin, JM; Gallagher, L; Hadley, DM; Macrae, IM; Condon, B (My University, 2008)
Purpose: Investigation of MRI for non-invasive autopsy via measurements of serial changes in relaxation parameters of the rat brain during the post-mortem interval. Materials and Methods: Post-mortem relaxometry measurements were performed before and hourly after death for 24 hours on five control rats and five rats which underwent middle cerebral artery occlusion. Analyses were performed on representative regions of grey, white, and mixed grey/white matter structures. Results: Significant decreases in both T1 and T2 values were measured in all areas in the control group within 24 hours of death. In the stroke animals, T2 differences between normal and ischaemic striatal tissue decreased by 11?4% (p<0.01), with a complete convergence of T2 values observed between ischaemic striatal tissue and non-ischaemic cortical tissue. Conclusions: Lesion conspicuity and the ability to differentiate between different tissue compartments are significantly affected by post-mortem interval, and alterations to pulse timing parameters will be necessary if the sensitivity of MRI to detect CNS diseases in post-mortem tissue is to be maintained. Indeed in the case of stroke at least, convergence of T2 values with normal tissue post-mortem indicates that T1 weighted images may be more sensitive to the presence of such lesions.
PUBLISHED
Keywords: post-mortem; virtual autopsy; MRI; stroke